75. Absent cardiac and muscle sympathetic nerve activities involvement in Ross syndrome: A follow-up study. Issue 12 (December 2017) - Donadio, V.; Fileccia, E.; Cortelli, P.; Liguori, R.
Abstract : Ross syndrome (RS) is a rare disorder characterized by selective involvement of post-ganglionic skin sympathetic nerve fibres with absent cholinergic sudomotor fibres as hallmark of the disease. It is still not well defined whether autonomic dysfunction remain localized to skin fibres or it affects also cardiovascular autonomic system. To clarify this aspect, we report a cardiovascular autonomic system follow-up study in 4 patients affected by Ross syndrome. We studied 4 patients affected by RS for a follow-up mean period of 5 years (range 1–10 years). All patients complained of anhydrosis with heat intolerance and showed areflexia and tonic pupil on neurological examination and absent cholinergic sudomotor fibres on skin biopsy. All patients underwent cardiovascular reflexes (CVR, head-up tilt test, Valsalva maneuver, deep breathing, isometric handgrip) and microneurography recording of muscle sympathetic nerve activity (MSNA) from common peroneal nerve. CVR and MSNA resulted normal at baseline and unchanged over the follow-up in all patients although anhydrosis was usually widespread on patient's clinical re-evaluation. Our preliminary study shows that cardiovascular autonomic system is not affected in Ross syndrome differently from skin autonomic activity dysfunction which tend to progress over time.